Study of the Small Farmers, Marginal Farmers and Agricultural Labourers Projects Design, Schedules and Instructions - Planning Commission (Planning Commission, 1974)
The agricultural situation in the past few years kept all concerned preoccupied with efforts at increasing agricultural production. For tire sake of achieving this objective in the minimum possible time, areas and persons most favourably situated for the purpose were made use of. The benefits of participating in these intensive agricultural programmes were received largely by progressive farmers, who also happened to be big farmers.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India